Ekstrak Aplikasi Pupuk Cair Pelengkap Tithonia Diversifolia Untuk Pertumbuhan dan Produksi Mustard Hijau (Brassica juncea.L) - Hasan Asnawi; Armaini '; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research aims to determine the best  dose of the extract for growth and production Mustard Green ( Brassica juncea.L). The experiments conductedin the Agriculture Faculty, University of Riau from October to December 2011. Research used a completely randomized design with 5 treatments and 4 replications, namely T0: With out giving Tithonia diversifolia extract, T1: 1500 ml/plot, T2: 2000 ml/plot, T3: 2500 ml/plot and T4: 3000ml/plot. Parameters observed that plant height, leaf area, number of leaves, plant fresh weight, plant weight consumed per sample and root volume. The results  showed Tithonia diversifolia extract dose 3000ml/plot is best for the growth and production of  mustard green (Brassica junceae.L). Keywords: Plant Mustard Green, Liquid Fertilizer Complementary, Tithonia diversifolia